Development of chimeric receptor activator of nuclear factor‐kappa B with glutathione S‐transferase in the extracellular domain: Artificial switch in a membrane receptor. (19th December 2021) - Kawashima, Kanako; Hirota‐Tsukimachi, Mayuko; Toma, Tsugumasa; Koga, Ryoko; Iwamaru, Kana; Kanemaru, Yosuke; Yanae, Misato; Ahagon, Ami; Nakamura, Yurine; Anraku, Kensaku; Tateishi, Hiroshi; Gohda, Jin; et al.
Abstract: Various chimeric receptors have been developed and used for biological experiments. In the present study, we constructed three types of chimeric receptor activator of nuclear factor‐kappa B (RANK) with the glutathione S‐transferase (GST) protein in the extracellular domain, and stimulated them using newly synthesized chemical trimerizers with three glutathiones. Although this stimulation did not activate these proteins, we unexpectedly found that the chimera named RANK‐GST‐SC, in which GST replaced a major part of the RANK extracellular domain, activated nuclear factor‐kappa B (NF‐κB) signaling approximately sixfold more strongly than wild‐type RANK without the ligand. The dimerization of extracellular GST is considered to function as a switch outside the cell, and signal transduction then occurs. GST has been widely employed as a tag for protein purification; GST‐fusion protein can be conveniently captured by glutathione‐conjugated beads and easily purified from impurity. The present study is a pioneering example of the novel utility of GST and provides information for the development of new chemical biology systems. Abstract : We constructed three types of chimeric RANK with GST protein in the extracellular domain, and stimulated them using newly synthesized chemical trimerizers with three glutathiones. In this process, it was found that one chimera activated NF‐kB signaling stronger than wild‐type RANK without ligand, probably by dimerization of extracellular GST.